Phase Transformation of Zeolite P to Y and Analcime Zeolites due to Changing the Time and Temperature - Seyed Naser Azizi; Akram Alavi Daghigh; Maryam Abrishamkar (Journal of Spectroscopy)
In the present study, the synthesis of template free zeolite P under hydrothermal condition was investigated. The effects of parameters such as Si/Al ratios (3–45), crystallization temperatures (80–160°C), and cry (40–60 h) on the synthesis of zeolite P were studied. The phase transformation of zeolite P to two types of high crystallinity Y and analcime zeolites due to change of temperature was observed. The effect of temperature on the achievement of two different zeolite types (Y and analcime) with a constant initial synthetic composition under organic free synthesis of zeolite P was studied. The zeolitic products were characterized by X-ray diffraction, scanning electron microscopy, and IR spectroscopy techniques.